A Man of Words and Silence: A Siberian Intellectual’s Mixed Patterns of Communication - Toulouze, Eva (Estonian Literary Museum, the Estonian National Museum and the University of Tartu, 2023)
Yuri Vella (1948–2013) was a well-known personality in Western Siberia’s indigenous world.Unlike most Western Siberia indigenous inhabitants, Yuri Vella was exceptionally skilled with words. He used words in everyday life in order to achieve his goals, among which the main one was to protect his kin and neighbours in the forest from the destructions induced by the oil industry. He was able to hold his own in discussion with the oil industry representatives and to have the last word with them.But how did Yuri Vella use words in private life? That is what months of fieldwork sharing the hut he lived in with his wife allowed me to ascertain. I shall concentrate on patterns of speaking – how? with whom? – and silence in everyday life, outside the attention of an audience. Or was my presence in the hut enough of an audience to change his patterns? These reflections are what this article is about.